2020
DOI: 10.1177/1553350620917898
|View full text |Cite
|
Sign up to set email alerts
|

Can Electric Nose Breath Analysis Identify Abdominal Wall Hernia Recurrence and Aortic Aneurysms? A Proof-of-Concept Study

Abstract: Introduction. This pilot study evaluates if an electronic nose (eNose) can distinguish patients at risk for recurrent hernia formation and aortic aneurysm patients from healthy controls based on volatile organic compound analysis in exhaled air. Both hernia recurrence and aortic aneurysm are linked to impaired collagen metabolism. If patients at risk for hernia recurrence and aortic aneurysms can be identified in a reliable, low-cost, noninvasive manner, it would greatly enhance preventive options such as prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…To further eliminate possible exogenous VOCs, the first two minutes of each 5 min measurement were only used to rinse the air in the lungs. The remaining three minutes were used in the analysis [21]. To familiarise patients with the device, patients could perform a few in-and exhales to get acquainted with the Aeonose™ before the actual measurements started.…”
Section: Aeonose™mentioning
confidence: 99%
See 2 more Smart Citations
“…To further eliminate possible exogenous VOCs, the first two minutes of each 5 min measurement were only used to rinse the air in the lungs. The remaining three minutes were used in the analysis [21]. To familiarise patients with the device, patients could perform a few in-and exhales to get acquainted with the Aeonose™ before the actual measurements started.…”
Section: Aeonose™mentioning
confidence: 99%
“…Due to the lack of previous studies in this population, an exact sample size calculation for this pilot study was deemed unfeasible. For a standard proof-of-concept study with an electronic nose, 25 patients are required [21,34]. Therefore, in this pilot study we aimed to include at least 25 patients with FBSS who are treated with SCS.…”
Section: Sample Size Calculationmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent published proof-of-concept study, it has been shown that patients with recurrent hernia could be distinguished from healthy controls using the eNose. 79 With the possibility to detect patients at risk to develop an incisional hernia, surgeons should be persuaded to use prophylactic meshes in these patients. Nowadays, surgeons are reluctant to use prophylactic meshes, in fear of mesh infections, while these meshes should often directly be placed after a gastrointestinal procedure.…”
Section: Prevention Of Abdominal Wall Hernias and Adhesionsmentioning
confidence: 99%